1979
DOI: 10.1161/01.str.10.4.375
|View full text |Cite
|
Sign up to set email alerts
|

Role of adrenergic nerves in blood-induced cerebral vasospasm.

Abstract: Cerebral arteries have an abundant supply of adrenergic nerve fibers which are believed to release vasoactive substances responsible for the induction of cerebral vasospasm. To assess the importance of adrenergic nerves in this phenomenon, high doses (600 microgram/ml) of 6-hydroxydopamine (6-OHDA) were used to produce in vitro chemical sympathectomy in bovine middle cerebral artery. 6-OHDA reduced catecholamine fluorescence to undectable limits. H3-norepinephrine re-uptake was reduced to 1.5% of intact contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…On the other hand, Simeone et al [1979] induced denervation with 6-hydroxydopamine and found that there was little differ ence in the reactivity of the vessels to cate cholamines, 5-HT or whole blood. Toda et al [1977] examined the contractility of blood vessels in spasm obtained from dogs, and found that the vessel in spasm did not differ significantly from control preparations in re sponse to 5-HT, noradrenaline, histamine, or high potassium.…”
Section: Catecholaminesmentioning
confidence: 99%
“…On the other hand, Simeone et al [1979] induced denervation with 6-hydroxydopamine and found that there was little differ ence in the reactivity of the vessels to cate cholamines, 5-HT or whole blood. Toda et al [1977] examined the contractility of blood vessels in spasm obtained from dogs, and found that the vessel in spasm did not differ significantly from control preparations in re sponse to 5-HT, noradrenaline, histamine, or high potassium.…”
Section: Catecholaminesmentioning
confidence: 99%
“…(c) Neurogenic effects may certainly be in volved in any kind of CBF regulation [29][30][31][32][33][34][35][36] and in the development of cerebral vaso spasm as well [44][45][46][47][48][49][50][51]. Neurogenic stimuli may exert their effects upon any cerebral arteries, especially the larger ones which pos sess an abundant vasoconstrictor adrenergic nerve supply [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], Under normal condi tions, neurogenic regulation of CBF is pre cisely adjusted, and thus should not cause vasospasms disturbing normal blood supply to the brain.…”
Section: Physiological Stimuli Involved In the Development Of Cerebramentioning
confidence: 99%